Informing health policy in Japan: A mixed‐model estimation to compare the cost of illness of cervical cancer and endometrial cancer. Issue 4 (29th December 2015) - Hayata, Eijiro; Seto, Kanako; Kitazawa, Takefumi; Matsumoto, Kunichika; Morita, Mineto; Hasegawa, Tomonori
Abstract: Aim: The objective of this study was to inform Japanese health policy by comparing cervical cancer and endometrial cancer from the standpoint of economic burden and examining factors affecting future changes in economic burden. Methods: Using government‐based nationwide statistical data, we used the cost‐of‐illness (COI) method to estimate the COI from 1996 to 2011 and predicted future estimates for 2014, 2017, and 2020. Results: In 2011, the COI of cervical cancer was estimated at 159.9 billion yen and that of endometrial cancer was estimated at 99.5 billion yen. Assuming the current trends in health‐related indicators, the COI of cervical cancer is predicted to temporarily decrease in 2014 and then remain constant. Meanwhile, the COI of endometrial cancer is predicted to temporarily decrease in 2014 before returning to an upward trend. Conclusion: The COI of both cervical cancer and endometrial cancer is estimated to remain constant or increase in the future. The average age of death from cervical cancer is predicted to remain relatively young and the high human capital value of patients who die in their sixties is the most likely explanation for the lack of decrease in future COI. As women's participation in society continues to increase, the future COI may also increase. Regarding endometrial cancer, the increase in direct costs, particularly hospitalization costs, is a likely factor resulting in the increase in the COI. This is because women are surviving longer, and thus receiving care for longer durations, because of advancements in medical care.